# Question #d0859

Feb 1, 2018

$h = 15$

#### Explanation:

$4 \left(h + 3\right) = 6 \left(h - 3\right)$

$4 h + 12 = 6 h - 18$

$18 + 12 = 6 h - 4 h$

$2 h = 30$

$h = 15$

-Sahar:)

Feb 1, 2018

$h = 15$

#### Explanation:

Lets start with using the distributive property. You are going to multiply the number on the outside of the parenthesis with everything that is inside of the parenthesis. The steps for the first part of the equation which is $4 \left(h + 3\right)$ is going to be red, and the steps for the second part of the equation which is $6 \left(h - 3\right)$ is going to be blue.

$\textcolor{red}{4 \cdot h = 4 h ,}$ and $\textcolor{red}{4 \cdot 3 - 12}$. This is going to give you the first part of the equation which is $\textcolor{red}{4 h + 12}$.

Now lets do the next part.

$\textcolor{b l u e}{6 \cdot h = 6 h}$. and $\textcolor{b l u e}{6 \cdot - 3 = - 18}$. This gives you the second part of your equation. Now your equation looks like this...

$\textcolor{red}{4 h + 12}$ $\textcolor{g r e e n}{=}$ $\textcolor{b l u e}{6 h - 18}$.

The next step is to add 18 to both sides.

$\textcolor{red}{4 h + 12 + 18 = 4 h + 30}$, and $\textcolor{b l u e}{6 h - 18 + 18 = 6 h}$

This will now give you the equation of $\textcolor{red}{4 h + 30}$ $\textcolor{g r e e n}{=}$ $\textcolor{b l u e}{6 h}$

The next step is to subtract $4 h$ from both sides.

$\textcolor{red}{4 h + 30 - 4 h}$, and $\textcolor{b l u e}{6 h - 4 h}$

This will give you the answer of $\textcolor{red}{30}$ $\textcolor{g r e e n}{=}$ $\textcolor{b l u e}{2 h}$.

The last step is to divide both sides by 2.

$\textcolor{red}{30 \div 2}$ $\textcolor{g r e e n}{=}$ $\textcolor{b l u e}{2 h \div 2}$

$\textcolor{red}{15}$ $\textcolor{g r e e n}{=}$ $\textcolor{b l u e}{h}$

So the answer to the problem is

$\textcolor{p u r p \le}{h = 15}$